2022
DOI: 10.3390/v14071532
|View full text |Cite
|
Sign up to set email alerts
|

The Newly Identified Trichoderma harzianum Partitivirus (ThPV2) Does Not Diminish Spore Production and Biocontrol Activity of Its Host

Abstract: A new partititvirus isolated from a Trichoderma harzianum strain (T673), collected in China, was characterized and annotated as Trichoderma harzianum partitivirus 2 (ThPV2). The genome of ThPV2 consists of a 1693 bp dsRNA1 encoding a putative RNA-dependent RNA polymerase (RdRp) and a 1458 bp dsRNA2 encoding a hypothetical protein. In comparative studies employing the ThPV2-infected strain (T673) and a strain cured by ribavirin treatment (virus-free strain T673-F), we investigated biological effects of ThPV2 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…T. harzianum isolates infected by ThPV2 showed higher mycelial density and spore production, which would help virus dispersion in the environment. Furthermore, isolates of T. harzianum infected with ThPV2 inhibited many fungal pathogenic species in confrontation tests [ 93 ]. These results suggest that ThPV2 can be used as a biological control agent.…”
Section: Resultsmentioning
confidence: 99%
“…T. harzianum isolates infected by ThPV2 showed higher mycelial density and spore production, which would help virus dispersion in the environment. Furthermore, isolates of T. harzianum infected with ThPV2 inhibited many fungal pathogenic species in confrontation tests [ 93 ]. These results suggest that ThPV2 can be used as a biological control agent.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, according to the official "Master Species list" (version 2021_v3, published in November 2022) provided by the International Committee on Taxonomy of Viruses, mycoviruses are taxonomically classified within 25 different officially recognized families. The majority of them (included in 12 families) possess a positive sense RNA (+RNA) genome and are accommodated within the Given the ecological relevance and the biotechnological impact of the Trichoderma genus, it is somewhat surprising that their associated mycovirome was only recently investigated: the first studies in this context mainly identified mycoviruses possessing a dsRNA genome, some of which have been characterized at a molecular level by providing their complete genome sequence (9)(10)(11)(12)(13)(14)(15); while three of them were classified as members of the Partitiviridae family (10,12,15) and one as member of the Curvulaviridae family (13), the majority could not be assigned to any officially recognized viral family (unclassified dsRNA). More recently, also +RNA mycoviruses have been identified and characterized in Trichoderma, two belonging to the family Hypoviridae (16,17) and one to the newly proposed family Ambiguiviridae (18).…”
Section: Introductionmentioning
confidence: 99%
“…Wang and colleagues observed that the presence of Trichoderma harzianum partitivirus 2 (ThPV2) did not produce negative effects on the qualitative biocontrol performance of the fungal host, which instead showed a moderate but statistically significant improved biocontrol activity in experiments with cucumber seeds inoculated with Fusarium oxysporum f. sp. cucumerinum (15). In another study, focusing on Trichoderma harzianum partitivirus 1 (ThPV1), inhibition of growth in co-cultured Pleurotus ostreatus and Rhizoctonia solani increased in ThPV1-containing strains compared with ThPV1-cured isogenic strains and this was associated to a significantly higher β-1,3-glucanase activity, whereas chitinase activity was not affected (12).…”
Section: Introductionmentioning
confidence: 99%
“…( 6 – 9 ). There is also evidence to suggest that Trichoderma species can promote plant growth and induce systemic resistance ( 10 – 14 ). The comparative genomic studies of several opportunistic strains of Trichoderma revealed numerous properties, which can be associated with their ecological versatility but did not explain them ( 1 , 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The comparative genomic studies of several opportunistic strains of Trichoderma revealed numerous properties, which can be associated with their ecological versatility but did not explain them ( 1 , 15 , 16 ). In this study, we tested whether the soil strains of Trichoderma contain viruses as our previous studies showed that this may influence their phenotype ( 12 , 14 ).…”
Section: Introductionmentioning
confidence: 99%